Evaluación biológica de los lodos residuales usando frijol (phaseolus vulgaris) y haba (vicia faba) - Colín Cruz, Arturo; Mulia Muñoz, Emma; Gomeztagle Hidalgo, María Mercedes; Moreno Alcántara, Jaime (CIENCIA ergo-sum, 2017)
-